Ответы и объяснения

2013-10-02T17:30:08+00:00
(Х+27) -12 =42                                                                                                            Х+27 = 42+12                                                                                                            X + 27 = 54                                                                                                               X= 54-27                                                                                                                    X = 27                                                                                   
2013-10-02T17:33:35+00:00